2021
DOI: 10.1111/1755-0998.13352
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the efficiency of molecular species delimitation in a species‐rich insect family

Abstract: In the contest of global biodiversity loss, molecular species delimitation approaches can be very useful for accelerating species discovery through DNA taxonomy and inventory through DNA metabarcoding. In this study, the effect of some intrinsic factors on the efficiency of various single-marker species delimitation methods (fixed and variable nucleotide distance thresholds, ABGD, ASAP, GMYC, mPTP) was tested on more than empirical datasets, derived from a set of 7,237 COI sequences attributed to leaf beetles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 85 publications
11
38
0
Order By: Relevance
“…Also, the congruence between the different delimitation methods, although using the same data, was moderate. This is in line with graphical summaries of many DNA taxonomy studies that have shown rather inconsistent results among different species delimitation approaches using the same marker (see above; Bergsten et al, 2012; Magoga et al, 2021). However, some studies, particularly those with limited geographical (i.e., regional) scope in the northern hemisphere, showed almost perfect matches of MOTUs with morphospecies among nearly 90% of the studied species (Hendrich et al, 2015; Pentinsaari et al, 2014; Rulik et al, 2017).…”
Section: Discussionsupporting
confidence: 82%
“…Also, the congruence between the different delimitation methods, although using the same data, was moderate. This is in line with graphical summaries of many DNA taxonomy studies that have shown rather inconsistent results among different species delimitation approaches using the same marker (see above; Bergsten et al, 2012; Magoga et al, 2021). However, some studies, particularly those with limited geographical (i.e., regional) scope in the northern hemisphere, showed almost perfect matches of MOTUs with morphospecies among nearly 90% of the studied species (Hendrich et al, 2015; Pentinsaari et al, 2014; Rulik et al, 2017).…”
Section: Discussionsupporting
confidence: 82%
“…While bPTP infers 8, 6 and 5 species, respectively, ASAP delimits 5 species within Gf5, and single species within each Gf7 and Gf8. This is in agreement with previous works reporting a tendency of tree based methods to over split species within geographically structured lineages and/or lineages that are over sampled (Magoga et al, 2021; Mason et al, 2020). We evaluated morphological traits for the taxonomy of Geomitopsis in the Canary Islands at the level of the eight principle lineages within the obtained Bayesian tree (See Figure 2).…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, GMYC analysis reveals 26 hypothetical species among the group. The discrepancy in the results of species delimitation may indicate a greater conservatism of ASAP, ABGD, and bPTP over GMYC, which shows lower efficiency in data sets at the genus than at higher levels (Magoga et al 2021). Though spe-cies delimitation has been defined as a method that sometimes causes confusion about almost every aspect of the definition of the 'species' level (Stanton et al 2019), the problem with delineating species' boundaries at the tree top must be related to the low-level independent genetic differentiation of the third clade in our tree.…”
Section: Discussionmentioning
confidence: 98%